Understanding Irregular War: The Influence of Planning and Perceptions on Operational Outcomes - Pavilonis, Brigid. (2017)
Abstract: With its powerful fighting force and rich history of experience, the U.S. should be poised for success in irregular war. As the wars in Afghanistan and Iraq prove, however, the U.S. struggles to win these asymmetric fights. This dissertation examines the disconnect between apparent ability and ultimate success by examining three research questions, regarding the rationale for war, recognition of irregular war as a significant military operation, and conduct of an effective operations. These questions led to three major findings. First, I argue that U.S. policymakers often commit military troops to irregular wars without fully developing an understanding of the long term national security goals they wish to achieve. Absent a clear statement of the rationale for intervention as tied to long-term objectives, operational effectiveness inherently suffers. Second, the military's partial repudiation of small war combined with a lack of doctrinal guidance for soldiers in the field has consistently manifested itself in an awkward transition from combat to stabilization, which often preordains long-term strategic failure. As military forces transition from the kinetic to stabilization phase, soldiers on the ground often misstep as they are untrained and ill-prepared for these missions. Finally, the United States' lack of effective planning for irregular war derives from policymakers' failure to promulgate a timely and effective national policy, which addresses the unique challenges presented by irregular war. To succeed in irregular wars, I argue that U.S. policy makers must 1) ensure all involved agencies must adopt a "unity of effort" approach, 2) recognize the operation as a political-military effort, 3) achieve legitimacy with the indigenous peoples, and 4) effectively utilize strategic intelligence. Through these changes in approach and understanding, the United States will be better equipped to win the irregular wars of the future.; Thesis (Ph.D.)--Tufts University, 2011.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: Richard Shultz.; Committee: William Martel, and Joseph Vorbach.; Keyword: International Relations.